Adapting to Changing Landscape: Strategic Planning and Change Management in Islamic Higher Education - Abdullah, Abdul Haris; Mala, Abdurahman R; Tola, Baso; Nento, Shinta (JURNAL AL-TANZIM, 2024)
This study aims to analyze the concept and process of strategic planning that can contribute to the success and effectiveness of strategic planning in Islamic universities by following the steps of strategic change developed by John Moore Bryson. The background of this study is based on the fact that the university environment, especially Islamic universities, generally still needs significant breakthroughs in strategic planning. The mixed method is used to consider the aspect of academic usefulness. First, the mixed method strategy gradually expands the findings. Second, the mixed method strategy combines quantitative and qualitative data into one piece of information to obtain a comprehensive analysis. The research findings show that the strategy model is an effort to integrate the main objectives and policies of the organization into a series of actions that can be relied on in achieving the organization at a certain point. The results of this study are expected to provide an essential contribution by identifying the gap between the John Moore-Bryson model and the strategic change model in the organizational environment of Islamic universities.